Literasi Riset Komunikasi Secara Kuantitatif di Kalangan Remaja - Hadi, A. Sigit Pramono; Rakhmayanti, Risda; Fahrezah , Yudha (Indonesian Journal for Social Responsibility, 2025)
The world of youth is a world that is still unstable. This is related to their cognitive and personality conditions which are still in the stage of development. In this situation, teenagers are exposed to massive social media exposure and conditions of intense social interaction with their peer groups. Various social and communication phenomena are present in their daily lives, so they are required to have a good ability to understand them. In fact, many adolescents have a tendency to act asocially due to failure to understand the real situation. Adolescents need to be equipped with the ability to obtain valid data in order to understand their environment. This community service activity was carried out with the aim of providing quantitative communication research literacy for youth. The activity was carried out in mid-2023 at Gita Kirti 3 High School, South Jakarta, with the presence of 72 class XI students. In these activities it was clear that the phenomenon of the youth's instability mentioned above. After understanding the explanation about the basic method of collecting data quantitatively, they are invited to carry out a survey simulation with topics that are appropriate to the daily issues experienced, especially social and communication phenomena. The survey was conducted online and the results were analyzed together. The results of this simple survey are valid data that can be accounted for. Thus, they believe and believe in the data obtained so that there is no longer any doubt about the reality that is happening.